Integration of genome and transcriptome reveal molecular regulation mechanism of early flowering trait in Prunus genus (Prunus mume and Prunus persica) - Li, Ping; Zhang, Qin; Shi, Baosheng; Liu, Liu; Zhang, Xiaoman; Wang, Jia; Yi, Haihui (Frontiers in Plant Science, 2022)
Flowering time is crucial for the survival and reproduction. Prunus genus belongs to the Rosaceae family and includes several hundred species of flowering trees and shrubs with important ornamental and economic values. However, the molecular mechanism underlying early flowering in Prunus genus is unclear. Here, we utilized the genome and transcriptome of P. mume and P. persica to explore the transcriptional regulation mechanism of early flowering. Comparative genomics found that genes accounting for 92.4% of the total P. mume genome and 91.2% of the total P. persica genome belonged to orthogroups. A total of 19,169 orthogroups were found between P. mume and P. persica, including 20,431 corresponding orthologues and 20,080 collinearity gene pairs. A total of 305 differentially expressed genes (DEGs) associated with early flowering were found, among which FT, TLI65, and NAP57 were identified as hub genes in the early flowering regulation pathway. Moreover, we identified twenty-five transcription factors (TFs) from nine protein families, including MADS-box, AP2/ERF, and MYB. Our results provide insights into the underlying molecular model of flowering time regulation in Prunus genus and highlight the utility of multi-omics in deciphering the properties of the inter-genus plants.